Issue to the Legal Protection of the Use of the State Budget to Handling Covid-19 - Idayanti, Soesi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Covid-19 pandemic, which impacted the health, social, and economic sectors as a non-natural disaster, led the President to make efforts to handle it with state financial policies by stipulating Perpu Number 1 of 2020. Budget misuse during the Covid-19 pandemic should be punishable by the death penalty because carried out when the state is facing a precarious situation; however, in Perpu No.1/2020, the Government grants immunity rights state budget managers. This legal immunity needs to be studied as a standard-issue regarding the state budget to overcome the Covid-19 pandemic. This study aims to examine the pandemic's impact on state finances and how Government policies are in dealing with the Covid-19 pandemic. This study used a normative juridical approach with data obtained from the literature, and the results were analyzed qualitatively. The results showed that the Covid-19 pandemic resulted in the Government changing the output of the use of the state budget aimed at dealing with the pandemic and restoring the country's economic condition due to the pandemic; the legal solution is to stipulate Perpu Number 1 of 2020, which was then approved by the DPR and became Law Number 2 2020. At the technical, operational level, the Government has also issued various policy regulations as a follow-up to Law Number 2 of 2020, which is used as an effort to deal with precarious situations as a result of the Covid-19 pandemic, such as fiscal policy stimulus, taxes, social assistance, and policies. Adjustment of regional finances. The problem that was considered urgent due to the Covid-19 pandemic led the Government to stimulate immunity in Law Number 2 of 2020. However, this immunity is given following the principle of good faith for users of state finances